Hybrid one-dimensional nanostructures one-pot preparation of nanoparticle chains via directed self-assembly of in situ synthesized discrete Au nanoparticles - Walter, Marie V (Langmuir : the ACS journal of surfaces and colloids, 2012)
© 2012 American Chemical Society